2010
DOI: 10.1111/j.1440-1797.2010.01302.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphisms within the transforming growth factor‐β1 gene with diabetic nephropathy and serum cholesterol and triglyceride concentrations

Abstract: The 869 T > C and 915 G > C polymorphisms within the TGF-β1 gene were associated with DN+. Lower cholesterol and triglycerides levels were observed in TT homozygotes for the 869 T > C polymorphism. The TGF-β1 869 T allele seems to confer protection against DN+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
4
25
1
Order By: Relevance
“…While, significant associations were reported in Chinese [23], Caucasians Polish [22], and Mexicans [42], insignificant associations were reported in Asian Indians [43] and in Japanese [44]. Although the present study has no CC genotypes among selected DN patients, the significant increase in TC genotype in DN þ patients is in accordance with the meta-analysis study of Jia et al [45] on TGF-b1 T869C (codon 10) polymorphism.…”
Section: Discussionsupporting
confidence: 78%
“…While, significant associations were reported in Chinese [23], Caucasians Polish [22], and Mexicans [42], insignificant associations were reported in Asian Indians [43] and in Japanese [44]. Although the present study has no CC genotypes among selected DN patients, the significant increase in TC genotype in DN þ patients is in accordance with the meta-analysis study of Jia et al [45] on TGF-b1 T869C (codon 10) polymorphism.…”
Section: Discussionsupporting
confidence: 78%
“…Similar trends were reported by a study on an Egyptian population where frequency of C-allele was higher in cases (both total T2D and T2D with ESRD) as compared to controls, and the TC genotype was providing 2-2.7-fold risk towards T2D and ESRD development (El-Sherbini et al, 2013). TGF-b1 g.869T > C polymorphism was observed to provide risk towards DN in Mexican (Valladares-salgado et al, 2010) and Chinese populations (Wong et al, 2003) and towards ESRD in a North Indian population (Mittal and Manchanda, 2007). Contrarily, reports on German and Spanish populations concluded that 869T allele rather than C allele was associated with ESRD susceptibility (Babel et al, 2006;Coll et al, 2004).…”
Section: Discussionsupporting
confidence: 72%
“…The present report is the first study conducted in the population of Punjab and Jammu and Kashmir evaluating the association of these polymorphisms with the risk of developing ESRD in T2D patients. Most of the previously reported studies have compared T2D and DN with each other rather with healthy controls, which can give inconclusive association and moreover, the DN cases included were of all stages (from glomerular hyperfiltration to ESRD) ( Valladares- Salgado et al, 2010). So the present study enrolled only the last stage DN cases with ESRD and compared them with both T2D and healthy controls to get irrefutable results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valladares-Salgado et al 29 reported that TT genotype carriers of +869T/C polymorphism had lower cholesterol and triglycerides levels, and T allele carriers of +869 T/C polymorphism confer protection against diabetic nephropathy. Kowalewska-Pietrzak et al 30 reported that TT genotype carriers of À509 T/C polymorphism was a risk factor for renal scarring in primary vesicoureteral reflux (VUR), and was also associated with susceptibility to congenital uropathy.…”
Section: Discussionmentioning
confidence: 99%